Podcasting mundane practices of solidarity and resistance in post-migrant Sweden - Gustafsson, Jessica (MedieKultur: Journal of media and communication research, 2024)
Sweden is a post-migrant society where the suburbs of the largest cities in Sweden have become the symbol of failed integration in public debate and media. To broaden the representation, young people from the suburbs use podcasting to challenge and present their own perspectives. Based on content analysis and interviews with selected podcasters this article explores how they position themselves in relation to mainstream media and society by focusing on their distinct media practices. The study suggests that these podcasts can be perceived as sites of cultural production where the articulation of mundane practices of solidarity and resistances are central. It is illustrated in the content and the guests they invite; and reflected in how the podcasters articulate their aims and goals, as well as how they position themselves in relation to other actors and spheres.